Responsivitas Pelayanan Publik (Studi Kasus Pelayanan Pasien BPJS Rumah Sakit Umum Daerah Kabupaten Pohuwato - Rusni Djafar; Umar Sune (Universitas Islam Darul Ulum Lamongan, 2022)
The responsiveness of BPJS Patient Services at the Pohuwato District General Hospital is based on six indicators according to Zeithaml as follows: This responsiveness indicator includes attitudes and good communication from officers (doctors or nurses) of the Pohuwato District General Hospital to patients. Good attitude and communication from doctors or nurses at the Pohuwato District General Hospital is good, this is shown by a friendly, polite, and empathetic attitude shown by doctors and nurses to patients. This service accuracy indicator relates to the alertness and sincerity in answering patient questions and fulfilling patient requests at the Pohuwato District General Hospital which includes the readiness of doctors or nurses to answer questions and fulfill patient requests, the sincerity of doctors or nurses in answering questions and fulfilling patient requests is classified as good. This can be seen in the results of the interview, namely the existence of patients who feel comfortable being cared for because the services provided are swift and sincere.